Relationship between dosimetric leaf gap and dose calculation errors for high definition multi-leaf collimators in radiotherapy. (January 2018) - Kim, Jinkoo; Han, James S.; Hsia, An Ting; Li, Shidong; Xu, Zhigang; Ryu, Samuel
Abstract: Background and purpose: Dosimetric leaf gap (DLG) is a parameter to model the round-leaf-end effect of multi-leaf collimators (MLC) that is important for treatment planning dose calculations in radiotherapy. In this study we investigated on the relationship between the DLG values and the dose calculation errors for a high-definition MLC. Materials and methods: Three sets of experiments were conducted: (1) physical DLG measurements using sweeping-gap technique, (2) DLG adjustment based on spine radiosurgery plan measurements, and (3) DLG verification using films and ion-chambers (IC). All experiments were conducted on a Varian Edge machine equipped with HD120 MLC for 6X, 6XFFF, and 10XFFF (FFF: flattening filter free). The Analytical Anisotropic Algorithm was used for all dose calculations. Results: The measured physical DLGs were 0.39 mm, 0.27 mm, and 0.42 mm for 6X, 6XFFF, and 10XFFF respectively. The calculated doses were lower by 4.2% (6X), 3.7% (6XFFF), and 6.8% (10XFFF) than the measured, while the adjusted DLG values with minimum errors were 1.1 mm, 0.9 mm, and 1.5 mm. The IC measurement errors were < 1%, and the film gamma pass rates (3%/3 mm) were greater than 97% for the spine plans. Conclusions: The calculated doses were systematically lower than measured doses with the physical DLG values. It was necessary to increase the DLG values to minimize the dose calculation uncertainty. The optimal DLG values may be specific to individual MLCs and beams and, thus, careful evaluation and verification are warranted.